Investigation and Prevention of Officer-Involved Deaths. - Wecht, Cyril H. (CRC Press, 2010)
An in-depth examination of all the facets of investigating police-related deaths, this book includes coverage of death scene investigation for reconstruction. It discusses collection of physical evidence, interviews, medical examination of the decedent, psychological factors involving both parties, and litigation of alleged police misconduct. The authors create composite scenarios from their collective case studies, providing precise examples that are factual and to the point. The scenarios covered include: suicide by cop shooting, restraint asphyxia in-custody death, fatal accident resulting.